2007
DOI: 10.1007/s11829-007-9012-5
|View full text |Cite
|
Sign up to set email alerts
|

Taste perception in honeybees: just a taste of honey?

Abstract: The advent of the genomic era has opened new doors to understand the fundamental organization of living organisms and has therefore promoted a fertile field of comparative research that intends to identify similarities and differences between related and unrelated species at the genomic level. One of the organisms whose genome has been recently decoded is that of the honeybee Apis mellifera, enabling a direct comparison with another wellstudied insect, the fruit fly Drosophila melanogaster. It was reported tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 44 publications
0
25
2
1
Order By: Relevance
“…It may simply be that quinine is not an efficient negative reinforcer for ants, unlike vertebrates. Recent findings on honeybee taste support this idea (de Brito Sanchez et al, 2006;de Brito Sanchez et al, 2007). Behavioural and electrophysiological explorations of gustatory sensilla on the antennae of bees failed to detect any response to bitter substances, which would be perceived as being not so different from water.…”
Section: Discussionmentioning
confidence: 90%
“…It may simply be that quinine is not an efficient negative reinforcer for ants, unlike vertebrates. Recent findings on honeybee taste support this idea (de Brito Sanchez et al, 2006;de Brito Sanchez et al, 2007). Behavioural and electrophysiological explorations of gustatory sensilla on the antennae of bees failed to detect any response to bitter substances, which would be perceived as being not so different from water.…”
Section: Discussionmentioning
confidence: 90%
“…Nicotine gives nectar a bitter taste, but honeybees have been assumed to have poor taste perception, as they possess only ten gustatory receptors, compared to more than 60 gustatory receptors identified in other insects (Robertson and Wanner, 2006). Accumulating evidence, however, suggests that honeybees are indeed able to detect secondary metabolites Singaravelan et al, 2005;Wright et al, 2010), and their taste perception is likely to be more complex than assumed from the number of gustatory receptors (de Brito Sanchez et al, 2007 Wright et al (2010) have recently shown that gustatory receptors on the proboscis do respond to such substances. Honeybees are less likely to drink sucrose-quinine solutions presented to the proboscis as the toxin concentration increases (Wright et al, 2010).…”
Section: Feeding Response To Nectar Nicotinementioning
confidence: 99%
“…To address this question, we used absolute and differential conditioning of the proboscis extension response (PER), which was used to test associative learning (Takeda, 1961;Vareschi, 1971) and relies on the bees' behavior to extend their proboscis when their antennae, tarsi or parts of the mouth are touched with a sugar solution (de Brito Sanchez et al, 2007). The sugar solution represents the unconditioned stimulus (US) (Bitterman et al, 1983).…”
Section: Introductionmentioning
confidence: 99%